Produtividade de arroz irrigado em função do número de operações mecanizadas de nivelamento de solo - Ramão, Cleiton José (2016)
Rice is produced in all Brazilian states , and most of the national production is concentrated in the states of Rio Grande do Sul and Santa Catarina. In these states dominate the conventional cultivation system , minimum and pre-germinated system , both with different heights of water depth . In this sense, the objective of this study was to determine the variability in the time of irrigation water depth in the fields of rice and its correlation with yield components of culture in the number of mechanized land leveling operations. The experiment was conducted in the municipality of Itaqui / RS , in a commercial crop of rice , using two areas (plots) of 15 hectares in minimum soil tillage system . In each area was carried out a number of different ground leveling operations , consisting of one and two leveling operations (repetitions) with the aid of a mechanized group consisting of hydraulic tractor and plow . For both areas, we used a sampling grid (grid) of 1 hectare , for determining the following attributes: chemical soil properties , plant population , average height of water depth , number of panicles , productivity and milling yield . The data were submitted to descriptive statistical analysis and correlation by the method of Pearson, the probability level of 5 %. From the results it can be inferred that the irrigated rice yield and the average height of water depth were not influenced by the number of ground -leveling operations in the conditions under which the experiment was conducted . The largest observed correlation with productivity, is the number of panicles per area , but without significant interference in the final crop yield. The number of panicles is a factor to be observed when defining the density of sowing of the crop, because suffer direct influence of plant population. Correlations regarding the chemical properties of soil such as calcium and magnesium , with the productivity of irrigated rice , demonstrate the importance of these , to define management areas .